182PDurable response to second-line m-FOLFIRINOX for advanced pancreatic adenocarcinoma in patients with performance status of two or less. (24th November 2019) - Das, A; Dean, A; Travers, N; Johansson, M; Yusoff, I
Abstract: Background: The efficacy of FOLFIRINOX in the treatment of pancreatic adenocarcinoma is well known and documented. However, most published data involves young patients with a performance status ≤1 (ACCORD study). Thus, traditionally FOLFIRINOX has been regarded as a first line only treatment for patients with good performance status. Patients requiring second line therapy are not regarded as being fit enough to receive FOLFIRINOX. We have previously published our experience that m-FOLFIRINOX can be utilised safely in these individuals, with appropriate dose reductions. Our position has been supported by a subsequent systematic review (Tong et al.). This updated report of our dual institution experience adds further evidence supporting the use of m-FOLFIRINOX as a second line treatment for pancreatic adenocarcinoma. Methods: A retrospective analysis was conducted on patients with locally advanced or metastatic pancreatic adenocarcinoma from two institutions who received first-line gemcitabine plus nab-paclitaxel, followed by second-line m-FOLFIRINOX between December 2011 and July 2019. All patients had an ECOG performance status of 2 or less. Overall survival (OS) was estimated via the Kaplan-Meier method. Results: We identified 85 patients in our analysis, with 64% patients having metastatic disease at diagnosis. The median age of our patients at diagnosis was 65 (range, 26 – 81). The dose intensity of m-FOLFIRINOX was the following: 65% for oxaliplatin, 68% for irinotecan, 18% for bolus 5-fluorouracil (5-FU) and 68% for infusional 5-FU. The median OS of all patients was 46.0 months (95% CI, 35.0 – 68.0). The median OS of locally advanced and metastatic pancreatic cancer from diagnosis was 68.0 months (95% CI, 45.0 – 68.0) and 23.0 months (95% CI, 19.0 – 49.0), respectively. Conclusions: Our expanded case series continues to demonstrate the growing role of m-FOLFIRINOX as a second line therapy for advanced metastatic pancreatic cancer, after the failure of first-line gemcitabine plus nab-paclitaxel. We continue to suggest that formal clinical trials are needed to further investigate this efficacy. Legal entity responsible for the study: St John of God Hospital, Subiaco. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.